Effects of Treatment with Temsirolimus versus Interferon Alpha on Survival of Patients with Metastatic Renal Cell Carcinoma – Single-Center Real-World Experience - Ivan Levakov; Saša Vojinov; Miloš Maletin; Dimitrije Jeremić; Mladen Popov; Olivera Levakov; Dragan Grbić (Acta Clinica Croatica, 2024)
Vascular endothelial growth factor (VEGF) and mammalian target of rapamycin (mTOR) inhibitors are two main groups of drugs for targeted treatment of metastatic renal cell carcinoma (mRCC). Inhibition of angiogenesis and other growth pathways that are pivotal for tumor progression lead to significant improvement of survival in patients with mRCC. The main aim of this study was to compare the effects of temsirolimus (mTOR inhibitor) and interferon alpha-2a (IFN-alpha-2a) on overall survival (OS) and progression-free survival (PFS) in patients with T3 stage mRCC who developed lung metastasis in the first two years after radical nephrectomy. A total of 60 patients diagnosed with T3 stage renal cancer who developed metastases in the lungs within two years after radical nephrectomy were included in a prospective study conducted at the Department for Urology, Clinical Center of Vojvodina and partially retrospective study at the Oncology Institute in Sremska Kamenica. Patients were divided into two groups consisting of 30 patients according to treatment with temsirolimus or IFN-alpha. During the first year of treatment, OS of patients treated with temsirolimus was 23.33%, whereas in patients treated with IFN-alpha it was 16.67%. Median survival in patients treated with temsirolimus was 9.3 months, whereas in patients treated with IFN-alpha it was 6.9 months, yielding a statistically significant difference (p=0.028). Patients treated with temsirolimus showed a statistically significantly longer median PFS compared to patients treated with IFN-alpha (p<0.0085). In conclusion, temsirolimus therapy had a significantly positive effect on survival in patients with mRCC. Patients treated with temsirolimus showed significantly longer median survival and median PFS compared to patients treated with IFN-alpha.